2020
DOI: 10.1155/2020/6374014
|View full text |Cite
|
Sign up to set email alerts
|

Imrecoxib Inhibits Paraquat-Induced Pulmonary Fibrosis through the NF-κB/Snail Signaling Pathway

Abstract: Objective. In recent years, pulmonary fibrosis caused by paraquat poisoning is still concerned. However, no effective drugs have been developed yet to treat paraquat-induced pulmonary fibrosis. The aim of our research is to investigate whether imrecoxib can inhibit paraquat-induced pulmonary fibrosis and its possible mechanism. Methods. Extraction of primary pulmonary fibrosis cells (PPF cells) in vitro by the method of trypsin digestion. RT-qPCR and western blot were employed to measure the transcription leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…A previous study reported that activation of the NF-κB signaling pathway occurs in the lung tissue of patients with IPF and mice with pulmonary fibrosis ( 46 ). The results of the present study demonstrated that the protein expression levels of p-NF-κB were significantly increased in TGF-β1-induced MRC-5 cells, which was consistent with previous studies ( 45 , 46 ). Notably, PG or PG-derived components increase AMP-activated protein kinase (AMPK) signaling in numerous types of cell, such as macrophages and lung carcinoma cells, hepatocellular carcinoma cells ( 47 49 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A previous study reported that activation of the NF-κB signaling pathway occurs in the lung tissue of patients with IPF and mice with pulmonary fibrosis ( 46 ). The results of the present study demonstrated that the protein expression levels of p-NF-κB were significantly increased in TGF-β1-induced MRC-5 cells, which was consistent with previous studies ( 45 , 46 ). Notably, PG or PG-derived components increase AMP-activated protein kinase (AMPK) signaling in numerous types of cell, such as macrophages and lung carcinoma cells, hepatocellular carcinoma cells ( 47 49 ).…”
Section: Discussionsupporting
confidence: 93%
“…The NF-κB pathway is commonly regarded as a pro-inflammatory signaling pathway ( 43 , 44 ). Moreover, NF-κB is involved in the development and progression of fibrosis via regulation of transcription factors associated with fiber growth, such as platelet-derived growth factor and TGF-β1 ( 45 ). A previous study reported that activation of the NF-κB signaling pathway occurs in the lung tissue of patients with IPF and mice with pulmonary fibrosis ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…40 rats were randomly divided into 5 groups ( n = 8 per group) and treated as previously described [ 24 , 25 ]: (1) control group, rats received no PQ but saline; (2) PQ group, rats were intragastric administration with 30 mg/kg PQ; (3) 8 mg/kg GC group, rats received 8 mg/kg GC after administration of 30 mg/kg PQ; (4) 16 mg/kg GC group, rats received 16 mg/kg GC after administration of 30 mg/kg PQ; and (5) 32 mg/kg GC group, rats received 32 mg/kg GC after administration of 30 mg/kg PQ. The GC groups received intraperitoneal injections of GC at the same time every day for 5 consecutive days.…”
Section: Methodsmentioning
confidence: 99%
“…RLE-6TN cells were randomly divided into 5 groups ( n = 8 per group) and treated as previously described [ 24 , 25 ]: (1) control group, cells were cultured in DMEM; (2) PQ group, cells were treated with 20 μ M PQ for 4 h; (3) 1 μ M GC group, cells were incubated with 1 μ M GC for 24 h after PQ treatment; (4) 10 μ M GC group, cells were incubated with 10 μ M GC for 24 h after PQ treatment; and (5) 100 μ M GC group, cells were incubated with 100 μ M GC for 24 h after PQ treatment.…”
Section: Methodsmentioning
confidence: 99%
“…These studies suggest that imrecoxib has a noninferior analgesic efficacy to celecoxib with good tolerance. In addition, imrecoxib can alleviate pulmonary fibrosis caused by paraquat poisoning through the NF-κB/snail signaling pathway (Jin, 2020).…”
Section: Introductionmentioning
confidence: 99%